2021
DOI: 10.20870/oeno-one.2021.55.3.4706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-veraison irrigation on the phenolic composition of <i>Vitis vinifera</i> L. cv. ‘Xinomavro’ grapes

Abstract: ‘Xinomavro’ (the second planted red Greek variety behind ‘Agiorgitiko’) generally produces wines that are light in colour but with increased astringency, possibly related to grape flavonoid amount and composition; although irrigation is accepted as an effective means to enhance grape phenolic maturity, its role has not yet been sufficiently studied in the case of Xinomavro. This study aimed to determine the effect of post-veraison irrigation on berry anthocyanin and proanthocyanidin amount and composition, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Generally, the accumulation of total soluble solids per berry decreased with increasing the pruning level from minimal to severe, while increased with postveraison water stress from none to an intense. is result is in agreement with recently published works [18,33,[40][41][42][43], where higher crop loads per grapevine resulted in a limitation in the final sugar level attainable in the fruit at harvest. is phenomenon was also demonstrated by the studies in [44,45], who found that water deficit combined with increased crop load led to a significant reduction in the rate of sugar accumulation.…”
Section: Total Soluble Solids ( 0 Brix)supporting
confidence: 93%
See 2 more Smart Citations
“…Generally, the accumulation of total soluble solids per berry decreased with increasing the pruning level from minimal to severe, while increased with postveraison water stress from none to an intense. is result is in agreement with recently published works [18,33,[40][41][42][43], where higher crop loads per grapevine resulted in a limitation in the final sugar level attainable in the fruit at harvest. is phenomenon was also demonstrated by the studies in [44,45], who found that water deficit combined with increased crop load led to a significant reduction in the rate of sugar accumulation.…”
Section: Total Soluble Solids ( 0 Brix)supporting
confidence: 93%
“…Besides, since berry weight was significantly affected by pruning level and water stress, it can be concluded that the increase was associated with an increase in the skin:flesh ratio. is finding is in line with other authors [40,42,46] whom reported that the increase in total anthocyanins and phenols under heavy pruning was due to an increase in grape berry weight and biochemical response of the anthocyanin and phenol metabolic pathway to the induced signals caused by water stress which led to increase the total anthocyanin and phenolic concentration per gram and contents per berry. In other previous studies [26,41,45], correlation analysis of potential factors contributing to altered metabolism in the anthocyanin pathway showed that color was negatively correlated with vigour indices, canopy density, and stomatal conductance and positively correlated with light penetration into the canopy.…”
Section: Total Anthocyanins and Phenolssupporting
confidence: 92%
See 1 more Smart Citation
“…Measurements of SWP were performed on vines of IR and NIR treatments to verify the impact of the contrasting irrigation treatments on grapevine water status. Indeed, grapevine water status considerably differed between the IR and NIR treatments, with the SWP values for both ranging from −1.20 to −1.22 MPa and − 1.50 to −1.56 MPa, respectively (Supplementary Figures S2A,B), suggesting a higher water deficit for the NIR plants at harvest since SWP values at the range of −1.10 to −1.30 MPa are considered as a moderated water deficit, whereas values inferior to −1.50 MPa are representative for severe water deficit (Theocharis et al, 2021).…”
Section: Measurements Of Bunch Density and Water Statusmentioning
confidence: 99%
“…Grapevine origin is relevant in the wine industry because it is associated with the definition of wine quality . Agronomic and environmental characteristics, such as soil, and climate, irrigation practices, pruning techniques, and soil physicochemical properties, are the main factors responsible for origin differences . In this vein, “terroir” has been defined as the interaction between the plant (genotype), combined with environmental and human factors related to crop management and winemaking techniques at each site .…”
Section: Introductionmentioning
confidence: 99%